2019
DOI: 10.1093/mnras/stz1191
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the origin of the counter-rotating core in IC 1459 with KMOS and MUSE

Abstract: The massive early-type galaxy (ETG) IC 1459 is a slowly rotating galaxy that exhibits a rapidly counter-rotating kinematically decoupled core (KDC, R KDC ≈ 5 ≈ 0.1R e ). To investigate the origin of its KDC, we coupled large data mosaics from the nearinfrared (NIR)/optical integral field unit (IFU) instruments K-band Multi-Object Spectrograph (KMOS) and Multi Unit Spectroscopic Explorer (MUSE). We studied IC 1459's stellar populations and, for the first time for a KDC, the spatially resolved initial mass funct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 142 publications
(210 reference statements)
3
17
0
Order By: Relevance
“…B3, we see a clear counter-rotating core at the centre of IC 1459. This is well known and well studied (Franx & Illingworth 1988;Cappellari et al 2002;Prichard, Vaughan & Davies 2019). Counter-rotation has long been associated with galaxy mergers (see e.g.…”
Section: B1 Ic1459mentioning
confidence: 92%
“…B3, we see a clear counter-rotating core at the centre of IC 1459. This is well known and well studied (Franx & Illingworth 1988;Cappellari et al 2002;Prichard, Vaughan & Davies 2019). Counter-rotation has long been associated with galaxy mergers (see e.g.…”
Section: B1 Ic1459mentioning
confidence: 92%
“…The galaxy hosts an active galactic nucleus with two symmetric radio jets (Tingay & Edwards 2015). Stellar kinematics revealed the existence of a fast counter-rotating stellar core that might result from the accretion of counter-rotating cold gas streams in early times (Franx & Illingworth 1988;Prichard et al 2019).…”
Section: The Ic 1459 Groupmentioning
confidence: 99%
“…The MUSE data used in this work is the same cube presented and prepared as described in Prichard et al (2019). We briefly summarise the observations and reduction of the MUSE cube here.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…A recent optical (MUSE: Multi-Unit Spectroscopic Explorer, Bacon et al 2010) and infrared (KMOS: K-band Multi-Object Spectrograph, Sharples et al 2013) IFU study of IC 1459 investigated the evolution of the galaxy focusing on the stellar populations, initial mass function (IMF), and stellar kinematics (Prichard et al 2019). The stellar velocity dispersion revealed that IC 1459 is dynamically hot along the major axis, which is indicative of counter-rotating stel-lar components extending throughout the galaxy beyond the core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation